Curcumin mitigates fumonisin B1-induced ovarian toxicity in peak-laying ducks via hormone metabolic protection and enhanced reproductive resilience - Wang, L.; Liang, R.; Cao, Q.; Hou, Z.; Shah, A.M.; Deng, Q.; Li, X.; Li, J.; Chen, J.; Lukuyu, Ben A.; Saleemi, M.K.; Yang, L.; et al. (MDPI, 2026)
The objective of this study was to evaluate the protective effect of curcumin (Cur) on reproductive toxicity induced by fumonisin B1 (FB1) in laying ducks during the peak egg-laying period. A total of seventy-two 50-week-old Cherry Valley ducks were randomly assigned to four groups: control, FB1 (30 mg/kg), Cur (200 mg/kg), and Cur + FB1 (200 mg/kg + 30 mg/kg). The experiment lasted for 35 days. Our results showed that cur supplementation effectively restored the reductions in final body weight (p = 0.005) and oviduct length (p = 0.020) induced by FB1 exposure. Residual FB1 concentrations in serum, liver, and ovaries were markedly increased in the FB1-treated group, while Cur significantly decreased the FB1 residual in duck liver (p < 0.05). Meanwhile, Cur supplementation markedly counteracted the FB1-induced reductions in serum total protein, albumin, triglycerides, and high-density lipoprotein induced by FB1 exposure. Cur supplementation effectively regulated FB1-induced oxidative stress, inflammation, and endocrine disruption. Specifically, Cur lowered FB1-induced malondialdehyde levels (p < 0.010), attenuated interleukin-1β increase (p = 0.083), and reversed the reduction in immunoglobulin G levels. FB increased the levels of hormones associated with duck reproduction, including estradiol, follicle-stimulating hormone, and luteinizing hormone; in contrast, curcumin supplementation decreased the levels of these hormones (p < 0.010). Histopathological analysis revealed that Cur significantly alleviated the inflammation and necrosis in the liver, kidneys, ovaries, and oviducts induced by FB1. In conclusion, dietary Cur supplementation effectively alleviated FB1-induced reproductive toxicity in laying ducks by enhancing antioxidant capacity, improving lipid metabolism, and restoring hormonal homeostasis.